Multifunctional hydrogel encapsulated with baicalin for full-layer regeneration of drug-resistant bacteria-infected wounds after radiotherapy - Rui Yuan; Sa Du; Siyu Pan; Zhuoyuan Lin; Nan Zhang; Chenxi Zhang; Qiang Zeng; Yen Wei; Yuwei Wu; Lei Tao (Bioactive Materials)
The post-radiotherapy wounds are common in patients. The irradiation-induced reactive oxygen species (ROS) accumulation, nucleic acid damage, and inflammation greatly hinder wound healing. The irradiation-induced immunosuppression may further cause bacterial infection. At present, few dressings are available for infected wounds after radiotherapy (IWAR). In this study, a multifunctional hydrogel for IWAR has been developed by combining a positively-charged antioxidant polymer with the natural product baicalin. This hydrogel can smartly release baicalin under IWAR-like microenvironment and possesses broad-spectrum antibacterial properties. It has effectively prevented irradiation-induced intracellular ROS and nucleic acid damage to protect fibroblasts for tissue repair. In mice treated with IWAR, this hydrogel has inhibited infection caused by drug-resistant Pseudomonas aeruginosa, downregulated inflammation, and significantly accelerated wound healing (to more than 10 times the rate of untreated IWAR), achieving full-layer regeneration. This study obtains a multifunctional hydrogel for IWAR, and provides insights into the development of radiotherapy-related biomaterials.